HUBUNGAN ANTARA BERAT BADAN BAYI BARU LAHIR DAN PARITAS DENGAN RUPTUR PERINEUM PADA PERSALINAN SPONTAN DI RSIA â€œBunda arifâ€ PURWOKERTO TAHUN 2010 - Destiati, Lysa; Prabandari, Fitria (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2011)
Postpartum haemorrhage can happened by hurt of path delivery, that one of them can from rupture perineum. Rupture can happened at first delivery and not rarely at the next delivery. The causes of rupture perineum’s insidense, one of it by a big of newborn baby weight and parities. This research purpose to know a relationship between a newborn baby weight and parities with rupture perineum at spontaneous delivery at RSIA Bunda Arif Purwokerto in 2010. This research was descriptive correlation research with approachment cross sectional. The population of this research was all of spontaneous delivery mother at RSIA Bunda Arif and the sample used was purposive sampling that amount 252 peoples. The method of data analyze used Chi Square test. The known research results: 1) The most baby who born with spontaneous delivery was a enough weight newborn baby (BBLC) as much as (77 %). 2) The most of spontaneous delivery mother was delivery mother who multipara as much as (55,20%). 3)Spontaneous delivery mother who delivered, the most of them experience rupture perineum that was as much as (67,1%). 4) The result of newborn baby weight and rupture perineum’s statistic analyze obtained p-value as many as 0,000 < 0,05 that means Ho pushed away and Ha acceptance, while the result of parities and rupture perineum’s analyze obtained p-value as many as 0,000 < 0,05 that means Ho pushed away and Ha acceptanced. There is a relationship between a newborn baby weight and parities with rupture perineum at spontaneous delivery. Keywords : Newborn baby weight, parities, and rupture perineum